(untitled) (Proceedings of Faculty of Civil Engineering, 2023)
The paper presents the design process of a breakwater structure based on BIM in Velopin Bay, Mali Losinj. It highlights the importance of input data and the advantages of using BIM technology in parametric modeling of such structures. The complex geometry, terrain conditions and loads, in addition to wave-related problems, pose a challenge. The use of Allplan and Scia software enables efficient development and analysis of several alternative solutions to select an optimal design which meets the criteria of load-bearing capacity, usability and construction cost.